2005
DOI: 10.1080/13880200590951685
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Alternanthera caracasana.

Abstract: The antimicrobial activity of different extracts of Alternanthera caracasana. HBK against 11 bacterial strains and 1 yeast strain was evaluated. The ethyl acetate extract showed antimicrobial activity against Staphylococcus aureus., Staphylococcus epidermidis., Bacillus subtilis., Sarcina lutea., and one strain of Vibrio cholerae.. There was no antimicrobial activity against Candida albicans.. As a bioactive compound, 7-methoxycoumarin was identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…Traditionally, the various plant parts (stems, leaves, flowers, roots) of A. caracasana Kunth have been used to treat dysentery, diarrhea, and fever. The infusion of the plant is used as lavage or beverage in the traditional system of medicines ( Canales-Martínez et al, 2008 ). The aerial parts of A. Brasiliana (L.) Kuntze are indicated in the treatment of inflammation, pain, and various infections ( Hundiwale et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the various plant parts (stems, leaves, flowers, roots) of A. caracasana Kunth have been used to treat dysentery, diarrhea, and fever. The infusion of the plant is used as lavage or beverage in the traditional system of medicines ( Canales-Martínez et al, 2008 ). The aerial parts of A. Brasiliana (L.) Kuntze are indicated in the treatment of inflammation, pain, and various infections ( Hundiwale et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Canales-Martínez and the team had evaluated the antimicrobial effect of the hexane, chloroform, methanolic, acetone, and ethyl acetate extracts obtained from the aerial parts of Alternanthera caracasana Kunth and also isolated a bioactive compound, 7-methoxycoumarin. They observed that the ethyl acetate extract as well as 7-methoxycoumarin were active against various Gram-positive and Gram-negative bacterial strains, but inactive against Candida albicans ( Canales-Martínez et al, 2008 ). Phytochemical profiling of Alternanthera caracasana Kunth is still not done, leaving a scope for the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial potential of crude extracts from numerous plants has been evaluated by agar well assay [21,22] and MIC determined based on which anti-infective lead molecules are isolated for use as a therapeutic agent [23,24]. Antibacterial activity of the alcohol extract of stem bark of Picralima nitida was tested against Staphylococcus aureus ATCC 12600 [25], where crude extract had a MIC range of 25 -50 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…A.brasiliana, known as lancetilla, used by the indigenous community of Colombia (Tikuna of the upper Amazon) as an analgesic and to relieve gastrointestinal problems (6). Some species, such as A. caracasana HBK, present antimicrobial activity (7), besides being used to treat different diseases already mentioned (Aguilar, 1994).…”
Section: Introductionmentioning
confidence: 99%